ESTIMASI BIAYA DAUR HIDUP DAN OPTIMISASI HARGA PESAWAT TERBANG - Zain, Rais; Ahyarsi, Odi (Indonesian Journal of Aerospace, 2011)
Since the conceptual design phase, the estimate of airplane life cycle cost (LCC) is carried out to support a decision making process. The LCC consist of research, development, testing, and evaluation cost, where an airplane estimated price (AEP) is a part of this calculation. Furthermore, AEP is employed as a non linear objective funtion for developing a constrained optimization algorthm. Rosen’s gradient projection is applyed in the development of computer program named Cost Analysis implementing object oriented approach on Microsoft Visual C++ 6.0. In order to verify the application, some data of Ourania jet airplane were utilized for carrying out a case study. The result of Cost Analysis shows that the estimated LCC are similar to the reference. Also, the optimization problems can be solved by Rosen’s algorithm less than ten iterations.